Effect of Simvastatin Nanohybrid drug on Liver Tissue and Some of Oxidation Indicators in White Male Rats Induced with Hyperlipidemia - Sabour, Aseel Najah; Mtashar, Zainab Zaidan (Scientific Journal of Medical Research, 2020)
Objectives: This study was designed to determine the effect of the nanohybrid hypolipidemic of simvastatin drug on Liver tissue and some of oxidation indicators(GSH and MDA) in white male rats induced hyperlipidemia. Methods: The nanohybrid compound of the drug was initially prepared and diagnosed as the drug was loaded onto zinc oxide layers. Results: The results of the test showed the infrared spectrum FT-IR obtained many of the distinctive movements of the bonds and group. XRD also showed a new diffraction in the spectrum of the nanohybrid drug compared to the zinc oxide carrier spectrum, indicating that the drug under study was a nanohybrid drug. The results of the examination of the atomic force microscope revealed that the average diameter of the nanoparticles of the hybrid drug Sim-Zno was 92.28 nm. To test the effectiveness of this compound compared to free simvastatin, the current study included two experiments, the first experiment used 50 males of adult white rats divided into two groups, the first group (control) fed normal diet and distilled water, the second group was induced hyperlipidemia by feeding on (cholesterol 2%, bile acid salt 3% and lard fat 8%) for two months. It was ascertained of hyperlipidemia by measuring lipid profile, the results showed increased high blood lipid levels compared with control group. The second experiment divided the remaining animals from the second group in addition to the control group to five groups, control group considered as negative control, T1 group as positive control, T2 , T3 and T4 groups were administered with the free 40 mg/kg simvastatin drug , nanohybrid compound of the drug at a dose 40mg/kg and Zinc oxide at a dose of 30 mg/kg respectively and concurrently fed with high-fat diet for 30 days. The results showed a significant increase in the level of MDA and a significant decrease in GSH level in the T1 group (positive control) compared with negative control with many histopatholgical changes in the hepatocytes resulted from fat accumulation in it. Conclusion: Nanohybrid compound of the simvastatin have a role in improvement oxidation indicators levels and histopatholgical changes of liver by increasing the bioavailability of drug and increasing its absorption.